The Contribution of Foreign Borrowing to the New Zealand Economy - Anthony Makin; Wei Zhang; Grant Scobie (New Zealand Government, The Treasury, 2008)
New Zealand's unrelenting current account deficits, its trade performance and high external debt level remain central to ongoing economic policy debates. However, what has been overlooked in the discussion of New Zealand's economic relations with its trading partners is the positive contribution that foreign capital inflow makes to the nation's economic development. International trade in saving between New Zealand and the rest of the world has potentially contributed more to its economic growth than international trade in goods and services. This paper views New Zealand's current account deficits as symptomatic of an economic growth process in which the rate of the economy's capital accumulation exceeds its domestic saving rate. Expansion of the domestic capital stock attributable to foreign saving leads to higher national output and national income per head, net of the servicing cost of foreign capital.
Keywords: F30; 330; Foreign borrowing; national income; current account deficit; national wealth; New Zealand; Internationale Staatsschulden; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Nationaleinkommen; Vermögensrechnung; Neuseeland